Innovative approaches in the food industry: Microwave plasma technology and applicability in foods - Kasar, Hüsnü; Gökmen, Suleyman; Yetim, Hasan; Bozduman, Ferhat (International Society of Academicians, 2024)
[Abstract Not Available]
Keywords: Gıda Mühendisliği; Gıda Sürdürülebilirliği; Gıda Bilimleri (Diğer)